(untitled) (University Journal of Zoology, Rajshahi University, 2007)
Key words: Trichosanthes palmata; repellency; Tribolium castaneum; Tribolium confusum Univ. j. zool. Rajshahi Univ. Vol.24, 2005. pp. 31-34